(untitled) (Nigerian Journal of Technology, 2018)
ABSTRACT Welding within forty eight (48) hours of joint preparation will help to prevent porosity in weld deposited at a Gas Tungsten Arc Welding (GTAW) process. This research aims at preventing weld porosity and improving weld quality using diagnostic case statistics for percentage dilution. Poor process conditions due to faulty operator error, use of wrong techniques, use of incorrect consumables and the use of bad weld grooves, are the common causes of porosity in weld deposits. In order to achieve the objectives of this research, the response: percentage dilution is used with four input process parameters such as current, voltage, speed and gas flow rate to optimize percentage dilution. Eradication of weld porosity was achieved using a current of 160.5 Amperes, voltage 17.5Volts, speed 100.6mm/min and gas flow rate of 16.07 Lit/min with a value of 46.9% percentage dilution. An established result from literature survey corresponds with the results in this study. Keywords: Weld Porosity, diagnostic case statistics, Percentage dilution (D), Gas Tungsten Arc Welding process. http://dx.doi.org/10.4314/njt.v38i1.17